TECHNOLOGIES OF EXCURSION AND ACCOMPANYING SERVICE IN THE SPHERE OF TOURISM AND HOSPITALITY - Horb, K. M.; Korneyev, M. V.; Horozhankina, N. A.; Kucher, M. M. (Systems and Technologies, 2025)
The article is devoted to the analysis and systematization of technologies of excursion and accompanying services in the field of tourism and hospitality, under different interpretations of excursion and accompanying: firstly, as a tourist service, when mainly service technological techniques are used, secondly, as a method of training using primarily pedagogical techniques, thirdly, as a tool of advertising and popularization with a priority based on marketing tools and PR technologies. The common and distinctive features between an excursion and accompanying are substantiated, the concept of an excursion and accompanying event (EAE) is proposed. The author’s technological scheme of accompanying a typical one-day cognitive bus tour is given as an example and basis for the formation of standards of tourist accompanying in the conditions of the «economy of impressions».Individual services and in general the activities related to the preparation and conduct of excursions and accompaniment, as well as excursion and accompaniment support for tourist trips, educational, business and advertising events, are substantively and technologically complex operations that require a fairly wide range of professional knowledge, skills and personal characteristics of its providers, including high responsibility (including financial), awareness of operating Google maps and creating content for social networks, stress resistance and efficiency in making decisions, taking into account the huge range of possible unforeseen situations during the trip. The distinction between excursion and accompaniment depends on the ratio of excursion and accompaniment services. In modern conditions, it can be considered relevant to improve, create and implement national standards and educational, methodological and instructional and regulatory materials on tourist support, taking into account international standards. But both the excursion and the tourist travel program as a whole are the result of a creative process, where creativity, unusualness and an individual approach are valued. Therefore, the processes of excursion and support services cannot be subjected to absolute formalization. In standardizing of the technological processes of tourist accompaniment and conducting excursions in the conditions of the «experience economy», it is worth finding a «golden mean» between ensuring high quality services and manifestations of creative imagination and creativity.